Efficacy of modified diode transscleral cyclophotocoagulation in patients with painful neovascular glaucoma secondary to retinal vein occlusion (Ukrainian Journal of Ophthalmology, 2025)
Purpose: To assess the efficacy (success rate) of modified diode transscleral cyclophotocoagulation (TSCPC) in patients with painful neovascular glaucoma (NVG) secondary to retinal vein occlusion (RVO).Material and Methods: This prospective, single-center cohort study included 62 patients (62 eyes) with NVG secondary to RVO. Best-corrected visual acuity (BCVA), the number of intraocular pressure (IOP)-lowering medications, laboratory characteristics and pain scores were assessed. A diode laser TSCPC with a fiber optic G-probe was performed at a power of 1,000 mW for duration of 1.5 s (corresponding to 1.5 J/pulse). Post-TSCPC measures of success included IOP between 10 and 21 mmHg or a reduction in IOP of ≥ 30% from baseline IOP, no ocular pain and improvement in or maintenance of BCVA.Results: At 12 months after TSCPC, the IOP decreased by 48% (р = 0.000). Eight (13%), 18 (29%), and 7 (11%) eyes received two, three, and four CPC sessions, respectively. Post-TSCPC complications included long-term inflammation was noted in 6 eyes (9.7%) and hyphema in 1 eye (1.6%). Multivariate regression analysis demonstrated that TSCPC success depended on the baseline IOP (р = 0.01), number of local IOP-lowering medications (р = 0.03), and presence of preoperative complications (р = 0.02), and was associated with a D-dimer value < 0.55 mg fibrinogen equivalent units/l (р = 0.01). Panretinal laser photocoagulation performed early (within 3 months) after RVO and combined with antiangiogenic therapy did not prevent NVG, but contributed to the success of TSCPC for NVG.Conclusion: The success rate of modified diode TSCPC in patients with painful NVG secondary to RVO at 12 months was 71%. Modified diode TSCPC in painful NVG secondary to RVO appears to be safe in terms of the absence of serious complications (hypotony and phthisis bulbi). TSCPC success depends on the presence of ophthalmic and systemic complications which should be treated.
Keywords: diode laser; transscleral cyclophotocoagulation; neovascular glaucoma; retinal vein occlusion; intraocular pressure; retina